Public administration and private management: is there a difference? - Chandler, J.A
In Britain academics are facing certain questions in designing a public administration course, whether to welcome or avoid the managerial business studies approach. The author analyses the arguments for both, the private and public enterprise. He concludes that there is need for most traditional business management syllabuses to take on some of the concerns of the public administrators. The public administrators should advocate its superior qualities as the foundation of study, education and training in the direction of large scale enterprise, irrespective of the fact that it lies in public or private domains. The public administrator should also not only have the ability to implement policy efficiently
Keywords: U.K; Management; Public Administration